Immediate and Long-Term Results of Treatment of Aneurysms of Ascending Aorta and Aortic Arch and Substantiation of Tactical Approaches to the Treatment Based on the Obtained Results - KravchenkoVitalii І. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Acute aortic dissection is a formidable disease. Its prevalence increases due to the population aging, as well as wider awareness of physicians about this pathology. The aim. To analyze immediate and long-term results of surgical treatment of aneurysms of ascending aorta and aortic arch and to determine optimal methods of correction of these lesions in order to improve the results of surgical treatment. Materials and methods. This was a comparative analysis of immediate and long-term treatment outcomes in 419 patients with aneurysms of ascending aorta and aortic arch. A comparative analysis of the results of treatment of two groups of patients was performed: the comparison group of 157 people operated before 2013, and the main group of 262 patients operated since 2013 using modified methods of aortic surgery. Results. The study showed significant reduction in the left ventricular dilatation according to echocardiography and satisfactory postoperative course in patients of both groups. Patients with valve-sparing aortic prosthetics had better results than those who underwent valve replacement surgery. Hospital mortality decreased from 17.2% to 5.3%. Analysis of long-term results showed that supracoronary aortic prosthetics with aortic valve plasty and elimination of the intimal tear zone make it possible to carry out effective aortic reconstruction. Due to events in the long run, regular lifelong monitoring is required. The analysis also showed that individualized approach to the choice of surgical tactics for the correction of aortic insufficiency in patients with aortic root and ascending aortic pathology allows to achieve comparable results in the immediate and long-term follow-up. Despite the complexity of the applied correction methods, the developed methods of surgical treatment of ascending aortic aneurysm (AAA) and aortic arch aneurysm and methods of protection of brain and visceral organs allowed to keep hospital mortality and the number of complications at the same level corresponding to one of the best world results. This gives hope for a good result in the long-term follow-up. Conclusions. Aneurysm of ascending aorta and aortic arch is a formidable life-threatening disease, and its only non-alternative treatment option is surgery. The optimized approach to the treatment of patients in the main group allowed to obtain better immediate and long-term results of surgical treatment and reduce postoperative complications from 34.4% to 8.4% and hospital mortality from 17.2% to 5.3%. Comparative analysis of long-term results in the studied groups showed more encouraging indicators of quality of life and life expectancy in patients when using modified surgical techniques, protection of the brain and visceral organs. We hope to get a final assessment of these data in the further study of the condition of these patients in the long-term follow-up.